Extensive Reading for Indonesian Learners’ Linguistic Background - Syofia Delfi; Hamidah Yamat (Universitas Negeri Padang, 2014)
The benefits of extensive reading for EFL students majoring in English have been studied in terms of the implementation of extensive. In Indonesia, there are not so many studies in the area of extensive reading and it is difficult to find out the study about the exploration of the use of extensive reading. This article is based on background and the main discussion of extensive reading for a study about “the exploration of the EFL Indonesian students’ experience in developing English competence”. The study is conducted to answer the research questions; (1) How is extensive reading being taught in classrooms? (2)What are the Indonesian EFL learners’ extensive reading experiences? (3) How does extensive reading develop the Indonesian EFL learners’ English language competency? In order to answer these questions, linguistic background of Indonesian students is needed to be studied thoroughly, therefore, it is inspired this article. The purpose of this article is to discuss the use of extensive reading for Indonesian students’ linguistic background. It will be discussed why extensive reading is expected to be experienced by Indonesian students, especially the students majoring in English. It focuses on Indonesian learners’ linguistic background, extensive reading, and the use of extensive for Indonesian learners’ linguistic background.